2018
DOI: 10.7249/rr2298
|View full text |Cite
|
Sign up to set email alerts
|

Ready or Not? Assessing the Capacity of New York State Health Care Providers to Meet the Needs of Veterans

Abstract: This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For information on reprint and linking permissions, please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…4 Conversely, whether non-VA care will have capacity or capability to meet the unique needs of veterans-especially for mental health-remains uncertain. 5 The VA has, for decades, aligned services with healthcare needs unique to veterans, veteran trust in the VA remains high, and most eligible for VCP choose to wait for VA care. 6 Development of enhanced shared decision-making approaches between veterans and their providers will therefore be essential.…”
mentioning
confidence: 99%
“…4 Conversely, whether non-VA care will have capacity or capability to meet the unique needs of veterans-especially for mental health-remains uncertain. 5 The VA has, for decades, aligned services with healthcare needs unique to veterans, veteran trust in the VA remains high, and most eligible for VCP choose to wait for VA care. 6 Development of enhanced shared decision-making approaches between veterans and their providers will therefore be essential.…”
mentioning
confidence: 99%
“…Though being a veteran is not a prerequisite for being an effective mental health provider for veterans, possessing the necessary cultural competence to work effectively with veterans is prerequisite. Tanielian () found that fewer than 30% of healthcare professionals in their study of mostly nonveteran providers were familiar with aspects of military and veteran culture. Only 13% received any formal or evidence‐based training regarding military and veteran culture.…”
Section: Negative Stigma and High Dropout Rates From Mental Healthcarementioning
confidence: 99%
“…It is also important to recognize that timely access to high-quality care is a national problem, but it is not limited to VA. MTFs have also had problems, and so has the private sector (Tanielian et al, 2018;Basu et al, 2012). The private sector is not always the "beacon of hope" for solving these issues.…”
Section: Other External Factors That May Affect Feasibilitymentioning
confidence: 99%